PENYELENGGARAAN ASIAN GAMES 2018 SEBAGAI UPAYA DIPLOMASI OLAHRAGA DAN MARKETING POWER INDONESIA - Angga Surya Christian (2020)
The Asian Games 2018 is an international multi-sporting events that has various potentials for Indonesia. The Asian Games 2018 can be a stage for Indonesia to promote its capabilities and power to the world community in order to encourage and increase its global appeal to achieve its interests. This research will discuss the use of the 2018 Asian Games as part of sports diplomacy to increase global attractiveness and capabilities of Indonesia as part of the marketing power element. The expected results from sports diplomacy and marketing power can be contribute to the growth and development of Indonesia's capabilities in the economic sector and Indonesia's foreign and domestic political interests.